A new ophthalmic pharmaceutical formulation, topical sulglycotide, enhances the ocular mucin secretion in desiccation stress-mediated dry eye disease - Lee, Hyesook; Jeon, Sangwon; Kim, Chae Eun; Park, Young Joon; Yang, Jaewook (Investigative Ophthalmology and Visual Science, 2019)
PURPOSE. The aim of this study was the investigation of the effect of sulglycotide (SOS), a polysulfated glycopeptide derived from porcine duodenal mucin, for the treatment of dry eye disease. METHODS. NOD.B10.H2b mice were exposed to an air draft for 10 days, and, simultaneously, scopolamine hydrobromide was injected subcutaneously. The mice were randomly divided into nine groups as follows: four kinds of SOS formulations and three kinds of commercial medicine. After 10 days of treatment, we estimated the effect of treatment on tear production, epithelium stabilization, mucin secretion, and inflammation. RESULTS. The desiccation stress significantly decreased tear production and corneal epithelium stabilization, as well as markedly decreased the numbers of goblet cells and mucin-stained cells in conjunctiva. However, the topical 4% SOS eye drops markedly increased tear production and corneal stabilization, which recovered to baseline levels. In addition, topical 4% SOS significantly induced an increase in the numbers of goblet cells and the expression of membrane-associated mucins including MUC1, MUC4, and MUC16, as well as the gel-forming mucin, MUC5AC. Furthermore, SOS formulations provided anti-inflammatory improvement in a dose-dependent manner. CONCLUSIONS. In summary, we suggest that a new ophthalmic pharmaceutical formulation, topical sulglycotide, enhances the ocular mucin secretion in dry eye disease and can be used as a new ophthalmic pharmaceutical material to treat dry eye disease.
Keywords: Administration, Ophthalmic; Animals; Anti-Ulcer Agents; Desiccation; Disease Models, Animal; Drug Compounding; Dry Eye Syndromes; Enzyme-Linked Immunosorbent Assay; Fluorescent Antibody Technique, Indirect; Goblet Cells; Immunohistochemistry; Mice; Mice, Inbred NOD; Mucins; Muscarinic Antagonists; Ophthalmic Solutions; Oxidative Stress; Real-Time Polymerase Chain Reaction; Scopolamine; Sialoglycoproteins; Tears; Conjunctival goblet cell; Dry eye disease; Inflammation; Mucin; Sulglycotide (SOS)